Exploring the causes of seafood fraud: A meta-analysis on mislabeling and price. (February 2019) - Donlan, C. Josh; Luque, Gloria M.
Abstract: Seafood mislabeling is receiving increased attention by civil society, and programs and policies to address it are being implemented widely. Yet, evidence for the causes of mislabeling are largely limited to anecdotes and untested hypotheses. Mislabeling is commonly assumed to be motivated by the desire to label a lesser value product as a higher value one. Using price data from mislabeling studies, Δmislabel is estimated (i.e., the difference between the price of a labeled seafood product and its substitute when it was not mislabeled) and a meta-analysis is conducted to evaluate the evidence for an overall mislabeling for profit driver for seafood fraud. Evidence is lacking; rather, Δmislabel is highly variable. Country nor location in the supply chain do not account for the observed heterogeneity. The Δmislabel of substitute species, however, provides insights. Some species, such a sturgeon caviar, Atlantic Salmon, and Yellowfin Tuna have a positive Δmislabel, and may have the sufficient characteristics to motivate mislabeling for profit . Atlantic Bluefin Tuna and Patagonian Toothfish have a negative Δmislabel, which could represent an incentive to mislabel in order to facilitate market access for illegally-landed seafood. Most species have price differentials close to zero—suggesting other incentives may be influencing seafood mislabeling. Less than 10% of studies report price information; doing so more often could provide insights into the motivations for fraud. The causes of mislabeling appear to be diverse and context dependent, as opposed to being driven primarily by one incentive. Highlights: Despite an increase in research and attention, little is known about the causes of seafood mislabeling. Results from a meta-analysis suggest that that causes of mislabeling are diverse and context dependent. Less than 10% of mislabeling studies report information on price. More attention to collecting price data could provide insights into the motivations for seafood fraud.